Optimal Seismic Design of Code-Compliant RC Moment Frames Through Analytic Hierarchy Process - Dindar, Ahmet Anıl; Bozer, Ali; Özkaynak, Hasan; Güllü, Ahmet; Müderrisoğlu, Ziya; Çalım, Furkan; Hasanoglu, Serkan (Teknik Dergi, 2025)
Proportion and detailing reinforcement for all structural members to resist internal forces occurring during strong ground motion are among the main seismic design criteria for reinforced concrete (RC) frame systems. Preliminary design is a crucial step in order to reach a proper final design. However, this stage mainly depends on the experience and intuition of the practitioner. The main aim of this study is to apply a multicriteria decision-making tool, namely Analytical Hierarchy Process (AHP) in selecting the optimal design candidate. A total of 76 optimal designed models out of 3,074 code-compiled buildings were selected based on the considered criteria via AHP procedure. During the analysis, the influence of selected design parameters such as site conditions, strength, ductility, and construction material on the optimal seismic design of these structures are investigated. Findings contribute to the optimization of structural design for both performance and monetary efficiency, while reducing the negative environmental effects.